The mixed layer modified radionuclide atmospheric diffusion based on Gaussian model - Li, Ting; Zheng, Xiaolei; Yu, Shengpeng; Wang, Jin; Cheng, Jie; Liu, Jie (Frontiers in Public Health, 2023)
The atmospheric diffusion is often accompanied with the complex meteorological conditions of inversion temperature. In response to the emergency needs of rapid consequence assessment of nuclear accidents under those complex meteorology, a Gaussian diffusion based model of radionuclide is developed with mixed layer modification. The inhibition effect of inversion temperature on radionuclide diffusion is modified in vertical direction. The radionuclide source intensity is modified by the decay constant. Results indicates the enhancement effect of mixed layer on the radionuclide concentration is reflected. The shorter the half-life of the radionuclide, the greater the effect of reducing the diffusion concentrations. The Kincaid dataset validation in MVK shows that compared with the non-modified model, the predictions of the modified model have an enhancement effect beyond 5 km, modulating prediction values closer to the observation values. This is consistent with the modification effects of mixed layers. The statistical indicators show that the modified model meets the criteria of the recommended model.